Families and communities responding to AIDS - Aggleton, Peter; Hart, Graham, 1957-; Davies, Peter (Peter M.) (Social aspects of AIDS., 1999)
By examining contexts as diverse as nuclear, extended and refugee family households and gay community networks, this book offers insight into the factors which lead to positive responses to AIDS, and those which trigger negative ones.